Exploring Early Childhood Linguistic Intelligence Through English Language Learning Methods - Gumarpi Rahis Pasaribu; Rani Arfianty; John Bunce (Innovations in Language Education and Literature, 2024)
This study investigates the effectiveness of interactive learning methods; playing, singing, and storytelling in enhancing linguistic intelligence among early childhood learners in English language settings. Adopting a qualitative case study approach, data were collected through classroom observations, semi-structured interviews with teachers and parents, and field notes. The findings reveal that interactive methods significantly improve children's engagement, vocabulary acquisition, and ability to construct simple sentences. Activities such as singing and storytelling not only boost verbal responses but also build children's confidence in using English both in and outside the classroom. Parents observed enhanced communication skills and self-confidence at home. Additionally, these methods contributed to cognitive development, fostering critical thinking and creativity. The study concludes that interactive English learning activities are instrumental in fostering linguistic intelligence in early childhood while providing a strong foundation for future academic and communication skills. Recommendations for integrating these methods into preschool curricula are provided, highlighting their potential for global adaptation in early language education.